ANALYSIS OF THE STUDENTS’ WRITING DIFFICULTIES OF ANALYTICAL EXPOSITION TEXT AT XI GRADE OF MA MIFTAHUL HUDA SUNGAI LUAR - Rosmina; Samsul Amri; Syafrizal (Program Studi Pendidikan Bahasa Inggris, 2021)
The purpose of this research is to know the students' writing difficulties of Analytical Exposition text at XI grade of MA Miftahul Huda Sungai Luar and the most dominant the students' writing difficulties Analytical Exposition text at XI grade of MA Miftahul Huda Sungai Luar. This research was achieved by conducting a descriptive quantitative study. The total population of this research was 51 students. The sample of this research was 51 students of eleventh-grade students of MA Miftahul Huda Sungai Luar. The researcher used total sampling to take the sample. The researcher gave a questionnaire to collect data. The questionnaire consists of 15 statements based on Writing Difficulties indicators. The questionnaire was using the Likert Scale. This questionnaire revealed that students' writing difficulties in analytical exposition text rely on high category, with 77.88%. The most dominant of the students' writing difficulties of Analytical Exposition was difficulty in developing ideas in long sentences. It means that they are difficulties in physiology with the average was 79.14% with high category. Based on the research results, the researcher concluded the Students had high difficulties Writing Analytical Exposition texts. They need to improve themselves to become easy to develop ideas in long sentences. The teacher's role is essential to guide them to be easier to develop ideas in long sentences.